Comparison of Pyrolysis and Combustion Processes of Vinyl Floor Panels Using Thermogravimetric Analysis (TG-FTIR) in Terms of the Circular Economy - Małgorzata Kajda-Szcześniak; Monika Czop (Energies, 2022)
The article analyzes the thermal degradation in the inert and oxidative atmosphere of waste vinyl panels, the main component of which is PVC. Both pyrolysis and incineration of plastic waste are difficult, complex and multifaceted processes due to several physical and chemical phenomena occurring during their performance. The coupled TG-MS (thermogravimetry-mass spectrometry) analysis combined with the Fourier transform infrared spectrometry (TG-FTIR) analysis was used to identify the decomposition mechanisms of waste vinyl panels. Thermogravimetric tests were carried out for two heating rates of 5 and 20 K/min in the temperature range of 40–1000 °C, mass losses were determined, and products resulting from thermal degradation were identified. It was found that the individual components decompose at different temperatures depending on the heating rate and the choice of an inert or oxidative atmosphere. Vinyl floor panels were treated in terms of secondary raw material, which, in the light of the circular economy, may constitute a potential energy or chemical resource.